Complete Remission After Single Radioiodine Therapy in Malignant Struma Ovarii With Bone and Lymph Node Metastases. (January 2019) - Seifert, Philipp; Gühne, Falk; Theurer, Sarah; Freesmeyer, Martin
Abstract : Abstract: A 67-year-old woman presented with malignant struma ovarii after radical bilateral salpingo-oophorectomy. The surgery revealed a 4.4 cm papillary thyroid carcinoma (follicular variant) within a right-sided ovarian teratoma. 124 I sodium iodide positron emission tomography / computed tomography and cervical ultrasound showed 2 slightly hyperfunctional thyroid nodules and several metastases, including bone metastases with intense iodine uptake. Thyroidectomy was necessary in preparation for radioiodine therapy and proofed the thyroid nodules to be benign. Complete remission was achieved by single radioiodine therapy (30 months of follow-up).